2015
DOI: 10.3989/arbor.2015.771n1009
|View full text |Cite
|
Sign up to set email alerts
|

Social Work with Older Adults in the United States

Abstract: This article examines ageing services in the United States, which are provided and financed through a mixed economy of care that includes government, the voluntary sector, and the private market. Because of substantial unmet needs, poorly coordinated systems, and social and economic disparities among older adults in the United States, social-work services have an important role to play in overcoming barriers to optimal functioning and emotional well-being in later life. Existing evidence suggests that the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Social work with older adults aims to ensure their independence, optimizing their physical, mental, and social functioning while maintaining proper quality of life. A guiding principle of social work involvement is to help older adults continue to “age in place,” meaning that older people continue to live independently at home in the community for as long as possible, which is the preference of most people ( Scharlach, 2015 ).…”
Section: Background: Social Work With Older Adults In Israelmentioning
confidence: 99%
See 2 more Smart Citations
“…Social work with older adults aims to ensure their independence, optimizing their physical, mental, and social functioning while maintaining proper quality of life. A guiding principle of social work involvement is to help older adults continue to “age in place,” meaning that older people continue to live independently at home in the community for as long as possible, which is the preference of most people ( Scharlach, 2015 ).…”
Section: Background: Social Work With Older Adults In Israelmentioning
confidence: 99%
“…Social workers can provide older men with necessary assistance aimed at improving and preserving their psychosocial functioning, such as counseling and guidance regarding individual and family problems and coping with old age-related issues. In addition, social workers can mediate between the older men and various social institutions in order to help them realize their rights and connect them to social activities such as volunteer work and daycare centers ( Makaros, 2006 ; Scharlach, 2015 ). Since previous studies have indicated possible barriers to seeking help from social workers by men, the current study sought to explore the association between several demographic factors, psychosocial factors, and factors related to attitudes and behaviors associated with seeking help, and the self-reported likelihood of seeking social worker help among older men.…”
Section: Research Toolsmentioning
confidence: 99%
See 1 more Smart Citation